127k views
4 votes
Evaluate the following function for (3, -1):
f(x, y) = 2x – 3y + xy^2

User Fforw
by
6.1k points

2 Answers

4 votes

In (3,-1) the first number is x and the second number is y.

Replace x and y in the equation and solve:

2x - 3y + xy^2 = 2(3) -3(-1) + (3)(-1)^2

Simplify:

6 + 3 +3 = 12

The answer is 12

User Stanojkovic
by
4.8k points
3 votes

Answer:

f(3, -1) = 12

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

f(x, y) = 2x - 3y + xy²

(3, -1) is x =3 and y = -1

Step 2: Evaluate

  1. Substitute: f(3, -1) = 2(3) - 3(-1) + 3(-1)²
  2. Exponents: f(3, -1) = 2(3) - 3(-1) + 3(1)
  3. Multiply: f(3, -1) = 6 + 3 + 3
  4. Add: f(3, -1) = 9 + 3
  5. Add: f(3, -1) = 12
User Till Hoffmann
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.